Comparative lipidomic analysis of synovial fluid in human and canine osteoarthritis. Issue 8 (August 2016) - Kosinska, M.K.; Mastbergen, S.C.; Liebisch, G.; Wilhelm, J.; Dettmeyer, R.B.; Ishaque, B.; Rickert, M.; Schmitz, G.; Lafeber, F.P.; Steinmeyer, J.
Summary: Objective: The lipid profile of synovial fluid (SF) is related to the health status of joints. The early stages of human osteoarthritis (OA) are poorly understood, which larger animals are expected to be able to model closely. This study examined whether the canine groove model of OA represents early OA in humans based on the changes in the lipid species profile in SF. Furthermore, the SF lipidomes of humans and dogs were compared to determine how closely canine lipid species profiles reflect the human lipidome. Methods: Lipids were extracted from cell- and cellular debris-free knee SF from nine donors with healthy joints, 17 patients with early and 13 patients with late osteoarthritic changes, and nine dogs with knee OA and healthy contralateral joints. Lipid species were quantified by electrospray ionization tandem mass spectrometry (ESI-MS/MS). Results: Compared with control canine SF most lipid species were elevated in canine OA SF. Moreover, the lipid species profiles in the canine OA model resembled early OA profiles in humans. The SF lipidomes between dog and human were generally similar, with differences in certain lipid species in the phosphatidylcholine (PC), lysophosphatidylcholine (LPC) and sphingomyelin (SM) classes. Conclusions: Our lipidomic analysis demonstrates that SF in the canine OA model closely mimics the early osteoarthritic changes that occur in humans. Further, the canine SF lipidome often reflects normal human lipid metabolism.